A DIFFERENCE VIEW TO ARCHITECTURAL HISTORIOGRAPHY IN TURKEY - Gurkas, Tayfun; Tanju, Bulent (YILDIZ TECHNICAL UNIV, 2011)
This thesis aims to do an analysis of the discourses in the texts of architectural history written between the Late Ottoman and Early Republican Periods. In inscriptive texts, forms of processes of this discourses called as totality narratives are examined. This thesis gives a place to several narratives such as nationalism, contextualism etc. instead of tracing only one narrative. These narratives are not handled one by one, contrary, embedded in a larger context. In the texts used in this thesis, it is interrogated how these discourses appear and what they answer. By this means, discourses are not evaluated as a reason but as the result.
Keywords: Historiography; totality narratives; Mimar Sinan; myth; Engineering